2018
DOI: 10.1007/s11548-018-1718-6
|View full text |Cite
|
Sign up to set email alerts
|

Precisely positioning the tip of an instrument inserted through an orifice with a free wrist robot: application to prostate biopsies

Abstract: Errors obtained by processing the clinical data reach 7.5 mm at the tip in average. Errors obtained with the laboratory apparatus drop from 2.4 mm in average to 0.8 mm when using real-time model update.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The latter are modeled as linear springs. This work was extended to instrument positioning by Chalard et al [11], where the deformation of the entry point is taken into account to refine the Jacobian matrix between the proximal and the distal ends of the instrument. Gijbels et al [12] introduce a robotic manipulator dedicated to assisting the insertion of a needle during retinal-vein cannulation.…”
Section: Related Workmentioning
confidence: 99%
“…The latter are modeled as linear springs. This work was extended to instrument positioning by Chalard et al [11], where the deformation of the entry point is taken into account to refine the Jacobian matrix between the proximal and the distal ends of the instrument. Gijbels et al [12] introduce a robotic manipulator dedicated to assisting the insertion of a needle during retinal-vein cannulation.…”
Section: Related Workmentioning
confidence: 99%
“…A main limitation of all these approaches is that it rely on a model that does not always correspond to the reality: in many cases, minimizing the interaction forces at the entry port is not equivalent to perfectly pivoting around a fixed point. In a previous work, [7], we have shown that when urologists perform a prostate biopsy while minimizing the forces in the rectum it is not possible to define a fixed point A around which the ultrasound probe rotates independently from the penetration depth. Therefore, minimizing −→ AR , either through installation, registration, or control, is not appropriate and may lead to non minimal forces at the insertion area.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the mechanical behavior of the insertion area also influences the tip position. In a previous paper, [7], we have evidenced this problem and proposed to identify the mapping between the wrist velocity, W and the tip velocityṪ . This identification allowed to compute the desired displacement of point W from the desired displacement at point T .…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the use of manipulator has a statistically significant increase in biopsy accuracy. 21…”
Section: Introductionmentioning
confidence: 99%